Reconstruction of lateral skull base defects with the trapezius myocutaneous flap: a description of two cases - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah (2006)
Introduction: Cancer involving the temporal bone may pose a difficult problem in both an oncologic and a reconstructive standpoint. These cancers are typically aggressive as well as locally advanced which require wide resections combined with parotidectomy and / or neck dissection resulting in extensive soft tissue and skin defects. Reconstruction of the surgical defects in temporal bone resection may vary from simple closure of the external ear canal to a complex flap coverage depending on the extent of surgical resection. The principles in reconstruction of lateral skull base defects are to maintain the symmetry, cosmesis of the lateral skull structures, to achieve dead-space obliteration and finally to have a quality vascularized tissue which able to withstand adjuvant radiotherapy treatment.